Laporan evaluasi geologi/geokimia proyek gondok endemik di lereng barat daya gunung merapi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
ABSTRAK A geological/hydrological investigation was conducted in the endemic goiter research areas in the Sawangan and Mungkid Sub-districts. The study included field observations and collecting rock/soil and water samples refresen ring different geohydrological conditions and rock formations of ground water pathways. The samples were analyzed for their major elements concentrations at the Chemical Laboratory of the Mount Merapi Research Section Office, Yogyakarta, using an atomic absorption spectrophotometric method. The results showed concentrations that were nor too different from the chemical contents of the Mount Merapi rocks.